Strategies for processing pumpkin seed oil: driyng, extraction, and encapsulation - Barros, Sâmela Leal (2024)
This comprehensive study investigates the optimization of the drying process of pumpkin seeds using ultrasound technology. It evaluates the efficacy of different encapsulating agents in protecting and releasing oil extracted from these seeds, focusing on their antioxidant properties, total phenolics, and instrumental color characteristics. The research highlights the underutilized potential of pumpkin seeds, emphasizing their exceptional nutritional value and exploring methods to extend their shelf life and improve their applicability in food products. Convective drying, despite inducing nutrient loss, is identified as a valuable technique for utilizing these residues. At the same time, oil extraction from pumpkin seeds is proposed as a promising approach due to its high nutritional value. The drying process was optimized through a 23 + 3 central points experimental design, using Statistica 7.0 software, and the effectiveness of ultrasound pretreatment in improving drying was evaluated despite observing vitamin C degradation. The analysis included the evaluation of parameters such as moisture content, water activity, drying time, pH, acidity, vitamin C concentration, protein content, color, antioxidant activity, and the profile of phenolic compounds, with the Page model demonstrating a better fit to the experimental data. Furthermore, the study examines the efficacy of different encapsulating agents - modified maltodextrin (Capsul - C), conventional maltodextrin (M), and a combination of both (CM) - in the protection and release of pumpkin seed oil, using Principal Component Analysis (PCA) to understand the correlations among the studied parameters. An in vitro gastrointestinal tract model was developed to simulate the oral, gastric, and intestinal phases, allowing for a detailed assessment of the microcapsules' release behavior. The results revealed significant differences in antioxidant capacity and oil release among the samples encapsulated with different agents, underlining the influence of the type of encapsulant on the oil's protection and release. Statistical analysis indicated that the lowest release rates occurred in the salivary fluid phase, suggesting that the microcapsule wall composition effectively protects against early degradation. This study contributes to food engineering and encapsulation technology, providing insights into the performance of encapsulating agents in protecting bioactive compounds and has practical implications for the development of functional food products, where controlled release of active ingredients is desirable. It paves the way for future investigations into optimizing encapsulation techniques for effectively delivering nutrients and bioactive compounds in the gastrointestinal tract.